(untitled) (Pathibhara Journal of Multidisciplinary Research, 2026)
Despite being a complex process deeply shaped by cultural and socio-political contexts, integrating psychology in social work has become a fundamental concern for improving human well-being. This study reviewed empirical studies to examine the application of psychology in social work across global, South Asian, and Nepalese contexts. In doing so, the study used library-based research methods and reviewed peer-reviewed journal articles, book chapters, and institutional reports. The literature was analyzed thematically to compare how psychological concepts are integrated into social work theories and practices. It seeks to identify common themes, contextual variations, and the specific challenges and opportunities present in Nepal. The study found that global literature demonstrates a well-established integration of psychology into social work, with increasing attention to humanitarian and cross-cultural applications. South Asian context reveals a critical movement towards decolonization and indigenization, emphasizing the centrality of family, spirituality, and community. Nepalese context, while emerging, shows promising developments in culturally adapting psychosocial interventions, yet grapples with challenges of professional identity, limited resources, and the dominance of Western models. In conclusion, application of psychology in Nepalese social work requires a thoughtful effort towards decolonized, culturally grounded approaches. This involves adapting interventions to local ethnopsychology, leveraging community-based resources, and addressing systemic barriers through policy integration and interdisciplinary collaboration.